The Reception of "De Rerum Natura" in the Poetry of Madame Deshoulières - Giles, Lacey (Studia z Historii Filozofii, 2021)
This paper explores Antoinette Du Ligier de la Garde Deshoulières’ philosophical poetry in context. The presentation of Epicureanism in various works, including Imitation de Lucrèce, her maximes, and idylls is analysed, considering both format and content choices and focusing on the ways in which both were used subversively. Her reception of Lucretius’ De Rerum Natura, as well as her social and political context inform this analysis. The challenges and limitations of producing work from the interstices of several conflicting identities are included to posit her case as an example of why women are under-represented in the history of philosophy.